Chronic Pain and Psychological Distress Among Older Adults: A National Longitudinal Study. (June 2018) - Bierman, Alex; Lee, Yeonjung
This research examines whether unobserved time-stable influences confound the association between chronic pain and psychological distress in older adults as well as how race and ethnicity combine with subjective social status (SSS) to modify the association. In a nationally representative longitudinal survey, holistically controlling for unobserved time-stable influences using fixed-effects models substantially reduces the pain–depression relationship and eliminates the overall pain–anxiety relationship. The association with depression is stronger for Black and Hispanic elders, illustrating a process of double-jeopardy. Black elders with severe pain experience lower anxiety, as do Black elders with moderate pain and low SSS, which we suggest may be due to the enervating effects of undermanaged pain. Black elders at high SSS experience greater anxiety with moderate pain. This research suggests that undermanagement of chronic pain among racial and ethnic minorities differentiates the association between pain and distress in late life and especially creates stronger associations with depression.